Masson's tumor on the forehead: A rare and Benign entity - Bhushan A Darkase; Atul M Dongre; Paras Choudhary; Uday S Khopkar (Wolters Kluwer Medknow Publications, 2019)
Masson's tumor is a rare, benign, reactive proliferating vascular lesion. The most commonly affected sites are the head, neck, and extremities. We present a 29-year-old male, a case of Masson's tumor over the forehead. Masson's tumor, with the involvement of the forehead is rare and intriguing in this case. Masson's tumor is a benign tumor that may get confused on histopathology with malignant tumors; hence, dermatologists need to understand this entity to avoid unnecessary confusion.